(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Youth-onset phenotypic type 2 diabetes mellitus (T2DM) often presents with high plasma glucose and hemoglobin A1c (HbA1c). Objective: To assess the relationship of β-cell secretory status and insulin resistance (IR) with plasma glucose and HbA1c at diagnosis in phenotypic T2DM of young. Methods: This cross-sectional study enrolled 72 newly-diagnosed youth-onset phenotypically T2DM patients [age range 19-29, median 27, inter-quartile range (IQR) 24-29 years; 40 (55.6%) female] to see insulin secretory status by fasting C-peptide and insulin resistance by visceral adiposity index (VAI) along with serum triglyceride/high-density lipoprotein cholesterol (TG/HDL-C) ratio. C-peptide was measured by chemiluminescence immunoassay. Result: Median fasting plasma glucose (FPG), 2h plasma glucose (2h-PG) and HbA1c of the participants were 10.8 (IQR 7.1-16.3) mmol/L, 18.0 (IQR 13.1-24.3) mmol/L, and 8.7% (IQR 6.7-11.0) respectively. All glycemic values inversely correlated with fasting C-peptide (FPG: ρ =-0.48, p<0.001; 2h-PG: ρ=-0.46, p<0.001; HbA1c: ρ=-0.44, p<0.001), body mass index (FPG: ρ =-0.39, p<0.001; 2h-PG: ρ=-0.35, p<0.001; HbA1c: ρ=-0.40, p<0.001) and waist circumference (FPG: ρ=-0.28, p=0.001; 2h-PG: ρ=-0.25, p=0.002 HbA1c: ρ=-0.29, p<0.001) whereas neither with VAI (HbA1c: ρ=-0.04, p=0.757; FPG: ρ=0.08, p=0.532; 2h-PG: ρ=0.20, p=0.099) nor with TG/HDL-C ratio (HbA1c: ρ=0.04, p=0.764; FPG: ρ=0.14, p=0.228; 2h-PG: ρ=0.14, p=0.074). In a linear regression model, adjusted for VAI, age and sex, each nmol rise of C-peptide was associated with 3.07 mmol/L fall (95% CI 4.73-1.41) of FPG, 3.22 mmol/L fall (95% CI 5.06-1.37) of 2h-PG and 1.51% fall (95% CI 2.38-0.64) of HbA1c. Conclusion: Plasma glucose and HbA1c of youth-onset phenotypic T2DM at the time of diagnosis is more influenced by β-cell secretory status than insulin resistance. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2024; 3(1): 09-15